CULTURAL RESILIENCE OF STUDENTS’ UNIVERSITY OF PGRI PALEMBANG BASED ON SUBCULTURE IN SOUTH SUMATRA - Syska Purnama Sari; Januar Eko Aryansah; Etty Pratiwi; Dewi Kartikasari (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2023)
Culture is one of the factors that influence resilience. Cultural diversity plays an important role for individuals in adapting to difficult conditions and situations. The purpose of this article was to analytically describe the differences in cultural resilience of students’ University of PGRI Palembang based on indigenous South Sumatran ethnic groups and immigrant ethnic groups in South Sumatran. The respondents of this study were students’ Guidance and Counseling study program of University of PGRI Palembang in semester II, IV, VI, and VIII of the indigenous tribes of South Sumatra with a total number of respondents as many as 80 students. The data collection method in this study used a cultural resilience questionnaire which was designed based on the theory developed by Clauss Ehlers and Reivich K and Shatte which consisted of six aspects of resilience, namely emotion regulation, impulse control, achievement, global coping, adaptive coping and socio-cultural support. The data analysis method used in this study by the Anova test. The results showed that there was no difference in resilience between students’ indigenous and immigrant in South Sumatran.